Developing Religious-Tolerance Culture based on Multiculturalism in Islamic Education Learning - Saihul Atho' A'alul Huda; Tri Siswatiningsih (SCHOOLAR: Social and Literature Study in Education, 2021)
This study raises the issue of developing a multicultural-based culture of religious tolerance in PAI learning at SD Negeri 1 Jombang. This study aims to describe the development of a multicultural-based culture of religious tolerance in PAI learning at SD Negeri 1 Jombang. This type of research is a qualitative descriptive research approach that contains explanations regarding the data obtained from the field. The research subjects were principals, teachers and students. The research was conducted in February - June 2021. The key instrument was the researcher himself, and the data collection techniques and data collection techniques used were observation, interviews and documentation. Data is analyzed by processing from data from sources, presenting data and drawing conclusions. Students at SD Nasionalegeri 1 Jombang come from different religious backgrounds, but in socializing they still uphold the attitude of religious tolerance. The development of a culture of religious tolerance carried out by school principals and teachers is carried out in the classroom and outside the classroom by 1) Providing opportunities for all students to take part in religious learning according to their religion 2) Creating a tolerant climate through religious holiday celebrations, prayers before and after learning, integration in religious learning, exemplary activities, habituation activities, routine activities include: flag ceremony, prayer together before the National Examination, spontaneity activities and conditioning activities.